008 PP: RESEARCHER-LED COLLABORATION BETWEEN PATIENTS AND CARERS, PALLIATIVE CARE AND EMERGENCY DEPARTMENT STAFF: AN EXPERIENCE-BASED CO-DESIGN PROJECT. (3rd March 2017) - Wright, R; Lowton, K; Robert, G; Grocott, P
Abstract : Objective: Increased numbers of older people with palliative care needs accessing the Emergency Department (ED) has challenged traditional care delivery processes. A doctoral Experience-based Co-design (EBCD) study sought to understand and improve palliative care experiences for older patients, their families and staff in the ED. Setting: An academically-based research nurse conducted the study at a large, urban ED. Study Design: Fifteen audio-recorded interviews with ED staff and ten filmed interviews with patient and family members exploring ED experiences were analyzed thematically. Findings were validated and priorities selected for service improvements through (a) five staff workshops (64 ED staff), and (b) individual sessions with patient-family members. A subsequent co-design meeting attended by patient-family members, ED, palliative care and service improvement staff identified shared improvement priorities and planned change activities. Findings: Mid-research process the researcher identified gaps in care practices and initiated conversations between the ED and palliative care staff resulting in: 1) re-design of the referral processes, 2) implementation of mandatory annual training for ED staff, and 3) initiation of routine communication between ED and palliative care teams. The co-design meeting led to 1) routine provision of information about the ED for patients, and 2) on-going interdisciplinary collaborations to improve palliative care based on patient-family recommendations. An objective, external researcher was helpful when misunderstandings were evident between disciplines. Conclusion: EBCD provided a flexible framework for researcher-led, clinically-based collaborative research within a complex environment with vulnerable patients. 'Co-design' processes facilitated ownership and engagement with the research by ED staff and patient-family participants, additionally enabling inclusion of palliative care staff.